Pengaruh Motivasi Terhadap Kinerja Karyawan Pada Ibu Kokom Katering Kecamatan Cikampek - Raihan Ramadhan Aziz; Santi Pertiwi Hari Sandi (CV. Aksara Global Akademia, 2023)
Catering Mrs. Kokom was established from 2019 until now, but there was a decline in sales at the time of the COVID-19 pandemic that caused the mentality and quality of human resources among employees to decline. In order to be able to improve the performance of employees, they need motivation or an incentive that makes them engaged and improves the quality of their work. The method used to compile this article uses descriptive and qualitative methods by interviewing business owners. The result is an increasingly motivated role to give reinforcement to desires that lead to better work performance and can guide individual behavior in the achievement of goals